Bihar Annual Plan Progress Report 1967 - Planning Commission (Planning Commission, 1970)
Statement showing progress of plan expenditure under major heads of development for the quarter ending 30th June, 1967.
Printed by the Superintendent Secretariat Press, Bihar, Patna